Listening can create magic. Issue 3 (May 2016) - Hodges, Dawn Z.
Abstract : My administrative assistant and I have been together for five years. She came into my office the other day and said, "You know those articles you write? You want an idea for one?" Never one to turn down some creative help, I said, "Sure!" She remarked that over the years she'd watched people come and go from my office. "I don't know what you do in there, but people always leave happier than they went in, " she said. "I call it magic! Write about that!" I thanked her for the compliment and the idea.